Neonatal mortality in dogs in a veterinary hospital in Brazil (Research, Society and Development, 2021)
Neonatology (the study of newborns) remains a little-explored specialty in medical clinics treating dogs. Therefore, neonatal mortality in dogs is high, and there is a lack of data on the subject in Brazil. The objective of this study was to record the neonatal mortality rate in dogs being treated at a Teaching Veterinary Hospital. We analyzed 69 (35 female and 34 male) newborn puppies born to 17 female dogs. The majority of the female dogs (94%; 16/17) and had dystocic parturition. Of the 69 puppies, only 30 (43.47%) survived the first 24 hours after birth. Based on these numbers, the neonatal mortality was considerably high at 56.52% (39/69), probably due to hypoxia that is known to be common in neonates with dystocic births. Given the above, it is concluded that assisted reproduction and prenatal examinations should be encouraged to reduce neonatal mortality in dogs.